Neisseria meningitidis Serogroup X ST-5799 (ST-22 complex) in Turkey: A unique pediatric case - Gönül Tanır; Yasemin Ozsurekci; Jay Lucidarme; Sevgi Yaşar Durmuş; Aiswarya Lekshmi; Özlem Akisoglu; Ahmet Emre Aycan; Ray Borrow; Mehmet Ceyhan (Taylor & Francis Group, 2018)
Although outbreaks of Neisseria meningitidis serogroup X occured in a couple of African countries, a limited number of serogroup X meningococcal cases were reported in America and Europe as well as Turkey. Additionally, serogroup X is still not represented in current conjugated meningococcal vaccines. Here, we describe the first pediatric case with meningitis caused by Neisseria meningitidis serogroup X ST-5799 (ST-22 complex) that formed a distinct lineage.